The therapist’s capacity to play - Tamir, Yossi (Natureza Humana - Revista Internacional de Filosofia e Psicanálise, 2019)
Playing is a central concept in Winnicott's developmental theory as well as a basic of human nature. In his last book –"Playing and Reality"- he also referred to the capacity to play as a central attribute of the clinical encounter, related both to the patient as well as to the therapist. However, Winnicott's intention as to the therapist's capacity to play remained unclear. This paper is an attempt to clarify Winnicott's intention, on the basis of the description of short therapeutic moments.